2013
DOI: 10.4236/ce.2013.47a2015
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of the Effect of Flipping Online Classes Using a Synchronous Interactive Online Tool

Abstract: Online instruction is a growing field, but there are concerns about lack of student engagement with mastery of content. Researchers at a small, private, southern university were concerned about increasing student engagement with online course content. A synchronous interactive online tool (SIOT) was added to six sections of online graduate education courses. Data was collected and analyzed from the university administered end of the course survey questions asking students to rate their course learning. Student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Reports of flipped online classes are not extensive and primarily show partial use of the full “flipped” structure. Carver, Todd, Hahn, and Mukherjee (2013) added a synchronous interactive in‐line tool to their existing online graduate education courses. When the tool was used to provide instruction related to student assignments, student response was significantly more positive than when the tool was not used.…”
Section: Literature Surveymentioning
confidence: 99%
“…Reports of flipped online classes are not extensive and primarily show partial use of the full “flipped” structure. Carver, Todd, Hahn, and Mukherjee (2013) added a synchronous interactive in‐line tool to their existing online graduate education courses. When the tool was used to provide instruction related to student assignments, student response was significantly more positive than when the tool was not used.…”
Section: Literature Surveymentioning
confidence: 99%
“…Instructors are more effective when they are student centered, expert, enthusiast and ethical (Carver et al, 2013). We do believe, however, that it is the preparedness of the instructors, their respect for the students, their command of the subject matter, and their availability to the students, that make a difference.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, Ng (2007) recognized that for effective on-line interaction between tutors and students, the technology tool should have low overhead in terms of the learning curve and the limitations on student-student interaction as well as student-tutor interaction. A study by Carver, Todd, Hahn, and Mukherjee (2013) found that the implementation of a synchronous interactive online tool by itself did not have a significant effect on students' learning. They found that the way the online tool is implemented is what made the difference.…”
Section: On-line Vs Face-to-face Instruction For It Coursesmentioning
confidence: 98%
See 1 more Smart Citation
“…Schroeder, Baker, Terras, Mahar, and Chiasson (2016) noted that graduate students desired connectivity with their instructors but connectivity with other students was not viewed as important, while undergrad students viewed both as important. Carver et al (2013) noted that the most important factor in using synchronous sessions for graduate students was not simply adding the sessions to the course, but to specifically use the sessions to support and expand course content. The difference in perspective between graduate and undergraduate students might be a significant contributing factor affecting voluntary attendance at synchronous sessions within this study.…”
Section: Analytics: a Data Mining Toolmentioning
confidence: 99%